1985
DOI: 10.1002/bbpc.19850891207
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Measurements at High Pressures and Low Temperatures VIII: Dielectric and Thermodynamic Properties of Cycloheptanol

Abstract: The thermodynamic and dielectric behaviours of liquid and solid cycloheptanol have been investigated using differential thermal analysis and capacitance measurements up to 10 MHz. The phase behaviour has been studied between 80 and 340 K and pressures up to 300 MPa. The well‐known phase transformations at 1 atm have also been observed at elevated pressures that enables to calculate the associated volume changes. The static and complex permittivities have been determined in the temperature range 240–310 K and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 5 publications
5
12
0
Order By: Relevance
“…From an earlier work [27], it seems to be clear that three different solid phases (denoted on cooling from the liquid state as I, II and III) could be identified down to about 170 K. Their transition temperatures (earlier consigned in Table 1 of the Ref. [27]) seem to be consistent with those obtained from several experimental techniques, in previous published works [21][22][23]25]. Preliminary X-ray diffraction experiments [27] revealed that phase I is simple cubic with a unit-cell parameter of 11.54(1) Å at 273 K (Z = 8) and phase II is tetragonal with unit-cell parameters of a = 19.487(2) Å and c = 11.7805(2) Å at 248.15 K (Z = 24).…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…From an earlier work [27], it seems to be clear that three different solid phases (denoted on cooling from the liquid state as I, II and III) could be identified down to about 170 K. Their transition temperatures (earlier consigned in Table 1 of the Ref. [27]) seem to be consistent with those obtained from several experimental techniques, in previous published works [21][22][23]25]. Preliminary X-ray diffraction experiments [27] revealed that phase I is simple cubic with a unit-cell parameter of 11.54(1) Å at 273 K (Z = 8) and phase II is tetragonal with unit-cell parameters of a = 19.487(2) Å and c = 11.7805(2) Å at 248.15 K (Z = 24).…”
Section: Resultssupporting
confidence: 81%
“…The molar volume changes at the III-to-II and II-to-I phase transitions, obtained from X-ray technique, are 0.07 and 1.15 cm 3 mol À1 , respectively. They are in accord with those obtained from pressure-temperature data using the Clausius-Clapeyron equation [23].…”
Section: Phasesupporting
confidence: 76%
See 3 more Smart Citations